Overexpression of lncRNA TCTN2 protects neurons from apoptosis by enhancing cell autophagy in spinal cord injury - Xiao‐dong Ren; Chun‐xiao Wan; Ya‐li Niu (FEBS Open Bio)
Neuronal apoptosis is the main pathological feature of spinal cord injury (SCI), while autophagy contributes to ameliorating neuronal damage via inhibition of apoptosis. Here, we investigated the role of tectonic family member 2 (TCTN2) long non‐coding RNA on apoptosis and autophagy in SCI. TCTN2 was down‐regulated in the spinal cord tissues of a rat model of SCI and in oxygen–glucose deprivation‐induced hypoxic SY‐SH‐5Y cells, while microRNA‐216b (miR‐216b) was up‐regulated. Overexpression of TCTN2 reduced neuron apoptosis by inducing autophagy, and TCTN2 was observed to negatively regulate miR‐216b. Furthermore, TCTN2 promoted autophagy to repress apoptosis through the miR‐216b–Beclin‐1 pathway, and overexpression of TCTN2 improved neurological function in the SCI rat model. In summary, our data suggest that TCTN2 enhances autophagy by targeting the miR‐216b–Beclin‐1 pathway, thereby ameliorating neuronal apoptosis and relieving spinal cord injury.